China in Central Asia : Measuring the Progress of the BRI - Nilsen, Harder Kristian (2023)
The Belt and Road Initiative (BRI), launched by China in 2013, has emerged as a global infrastructure and economic development strategy spanning diverse regions. This thesis investigates the potential for dependency on China resulting from BRI investments in partner countries. This thesis delves into the theoretical underpinnings of dependency theory and neomercantilism as a framework for understanding the implications of BRI engagement. By analyzing extensive academic literature, official documents, and research papers, the research seeks to discern empirical evidence of dependency dynamics. Central to this investigation are two early BRI partners, Kazakhstan and Uzbekistan, chosen as case studies due to their prolonged engagement with the initiative. These case countries offer a unique lens to assess the diversified impacts of BRI investments, including potential economic and political dependencies on China.